2021
DOI: 10.1186/s13046-021-02053-y
|View full text |Cite
|
Sign up to set email alerts
|

The CD112R/CD112 axis: a breakthrough in cancer immunotherapy

Abstract: The recent discovery of immune checkpoint inhibitors is a significant milestone in cancer immunotherapy research. However, some patients with primary or adaptive drug resistance might not benefit from the overall therapeutic potential of immunotherapy in oncology. Thus, it is becoming increasingly critical for oncologists to explore the availability of new immune checkpoint inhibitors. An emerging co-inhibitory receptor, CD112R (also called PVRIG), is most commonly expressed on natural killer (NK) and T cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 84 publications
(152 reference statements)
0
17
0
Order By: Relevance
“…It was reported that the combined CD112R and TIGIT blockade allowed diffusion of CD4+ T cells and increased the productions of cytokines such as IFN-γ, IL-2, IL-5, IL-10, and IL-13. Moreover, blockade to these two checkpoints led to restored cytotoxicity and expansion of CD8+ T cells [75].…”
Section: Tigit Signaling Pathwaysmentioning
confidence: 99%
“…It was reported that the combined CD112R and TIGIT blockade allowed diffusion of CD4+ T cells and increased the productions of cytokines such as IFN-γ, IL-2, IL-5, IL-10, and IL-13. Moreover, blockade to these two checkpoints led to restored cytotoxicity and expansion of CD8+ T cells [75].…”
Section: Tigit Signaling Pathwaysmentioning
confidence: 99%
“…TIGIT (T cell immunoglobulin and immune receptor tyrosine-based inhibitory motif domain) [ 357 ] is expressed by T cell populations [ 358 ] and NK cells [ 359 ] and binds both CD112 [ 360 ], which is expressed by DCs [ 361 ] and various non-immune cell types [ 362 , 363 ], and CD155 [ 358 ]. By using solubilized TIGIT, engagement of CD155 was demonstrated to result in Treg activation [ 364 ] and inhibition of DCs [ 358 ] and NK cells [ 359 ].…”
Section: Emerging Immune Checkpoints and Their Impact On Non-t-cell I...mentioning
confidence: 99%
“…Further NK cell co-inhibitory immune checkpoints also expressed by other immune cell types that are currently in the focus of interest are T cell immunoglobulin and mucin domain molecule 3 (Tim-3) [ 95 ], T cell immune receptor with immunoglobulin and ITIM domains (TIGIT) [ 96 ], and CD112 receptor (CD112R) [ 97 ]. Whereas Tim-3 recognizes galectin-9, HMGB1 and CEACAM1, the latter two are specific for the nectin family molecules CD112, CD113, and CD155 [ 98 ], as well as for the recently detected nectin-4 in the case of TIGIT only [ 96 ].…”
Section: Harnessing Of Autologous Nk Cellsmentioning
confidence: 99%
“…Regarding CD112R, it is a molecule considered as having a high potential in cancer immunotherapy and it has already been shown that its ligand CD112 has a diagnostic and prognostic value in several cancers of the digestive tract and others [ 97 ].…”
Section: Harnessing Of Autologous Nk Cellsmentioning
confidence: 99%